High Homocysteine Levels Are Associated with Cognitive Impairment in Patients Who Recovered from COVID-19 in the Long Term - Oner, Pinar; Yilmaz, Seda; Dogan, Serpil (Mdpi, 2023)
In this study, we measured the levels of depression and cognition in people recovering from COVID-19. Moreover, we aimed to investigate the relationship between depression and cognition levels by measuring homocysteine concentrations. It included 62 people recovering from COVID-19 (at least 3 months after positive RT-PCR) and 64 people without COVID-19 (control group). At first, the homocysteine levels of participants were measured. Beck Depression Inventory (BDI) and Montreal Cognitive Assessment (MoCA) were performed to collect data. Homocysteine levels of the group recovering from COVID-19 (x(-) = 19.065 mu mol/L) were higher than the control group (x(-) = 11.313 mu mol/L). There was no significant difference between the groups for BDI scores. The MoCA scores of the group recovering from COVID-19 (x(-) = 20.774) were lower than the control group (x(-) = 24.297). There was a negative high (r = -0.705, p < 0.001) correlation between homocysteine levels and MoCA scores. Linear regression analysis is shown to be significant, and the MoCA explanatory value of the variables in the model is 58.6% (p < 0.0001). A 1 mu mol/L observed increase in homocysteine level constituted a risk for a 0.765-point decrease in MOCA scores. In patients recovering from COVID-19, early interventions to high homocysteine levels may prevent cognitive impairments that may persist in the long term.
Keywords: COVID-19; homocysteine; cognition; depression; long term